2013
DOI: 10.1200/jco.2013.31.15_suppl.7034
|View full text |Cite
|
Sign up to set email alerts
|

Costs of allogeneic hematopoietic cell transplantation using reduced intensity conditioning regimens.

Abstract: 7034 Background: Reduced intensity (RIC) conditioning regimens have allowed older patients and those with comorbidities to receive hematopoietic cell transplantation (HCT). Methods: We analyzed medical costs from the beginning of conditioning to 100 days after HCT for 484 patients who underwent a RIC allogeneic HCT at Fred Hutchinson Cancer Research Center (FHCRC; n=147) and Dana Farber Cancer Institute (DFCI; n=337) from 1/2008 to 12/2010. Costs up to 2 years after HCT were analyzed for DFCI (n=311) as most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Costs related to hospitalization were the major contributors across the studies, and cost associated with initial hospitalization for HSCT was the main driver of total cost in the first 100 days post-transplantation [35]; medical staff costs, room and board, pharmacy, laboratory services, radiology, and blood products were the major cost contributors [36,37]. Recently, in a study of HSCT with RIC at 2 institutions, it was found that significant predictors for lower costs for the first 100 days included a diagnosis of lymphoma/myeloma and use of human leukocyte antigen-matched related donors, whereas grade II-IV acute GVHD was associated with higher costs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Costs related to hospitalization were the major contributors across the studies, and cost associated with initial hospitalization for HSCT was the main driver of total cost in the first 100 days post-transplantation [35]; medical staff costs, room and board, pharmacy, laboratory services, radiology, and blood products were the major cost contributors [36,37]. Recently, in a study of HSCT with RIC at 2 institutions, it was found that significant predictors for lower costs for the first 100 days included a diagnosis of lymphoma/myeloma and use of human leukocyte antigen-matched related donors, whereas grade II-IV acute GVHD was associated with higher costs [38].…”
Section: Discussionmentioning
confidence: 99%
“…24,29,30 Costs Baseline direct medical costs were derived from the 2016 Medicare fee schedule and the medical literature (Table 2). [36][37][38][39][40][41] Costs were converted into 2016 US dollars using the Medical Care component of the Consumer Price Index. Consistent with the Medicare pricing policy, we used 106% of the manufacturer's 2016 average sales price for drug costs.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
“…5 Arai 2013, 31 Kaloyannidis 2012, 32 used in previous studies. [38][39][40] The cost of monitoring included office visits and routine laboratory tests. Endof-life health care costs were estimated from published data on the cost of care in the last year of life for patients with cancer compared with the general Medicare population.…”
Section: Transition Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations